Preparation method for improving coercive force and temperature stability of neodymium-iron-boron magnet
By depositing the film using atomic layer deposition method on the surface of NdFeB magnetic powder, combined with orientation pressure, insulation sintering and tempering treatment, the problem of poor temperature stability of NdFeB magnets is solved, significantly improving the coercive force and temperature stability of the magnets, and reducing the amount of heavy rare earths.
Patent Information
- Application Number
- CN202510163313.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-15
AI Technical Summary
The temperature stability of neodymium iron boron magnets is poor, and the magnetic properties deteriorate at high temperatures. The traditional grain boundary diffusion process has problems such as low diffusion efficiency, limited depth and poor uniformity.
Atomic layer deposition method is used to deposit thin films on the surface of NdFeB magnetic powder, including Al, Cu, Er, Hf, Dy, Tb, Ga, La, Ta, Mg, Ti, Ir, Pt, Pd, Co or Ca, and the coercive force and temperature stability of the magnet are improved through orientation pressure, insulation sintering and tempering treatment.
It significantly improves the coercive force and temperature stability of the neodymium iron boron magnet, reduces the amount of heavy rare earth, is easy to operate, is easy to control, and maintains the residual magnetic induction strength and maximum magnetic energy production of the magnet.
Smart Images

Figure CN119833268A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth permanent magnetic materials, and in particular to a preparation method for improving the coercive force and temperature stability of a neodymium iron boron magnet. Background Art
[0002] As the third generation of rare earth permanent magnet materials, NdFeB permanent magnet materials have extremely high magnetic properties and are widely used in various fields of life, including power electronics, wind power generation, new energy vehicles, medical equipment, robots, etc. However, the temperature stability of sintered NdFeB magnets is poor. As the temperature rises, the magnetic properties deteriorate rapidly. In order to reduce the temperature sensitivity of the magnet, it is necessary to continuously improve the coercive force of the magnet and increase the Curie temperature of the magnet. In addition, application scenarios such as aviation drive motors require magnets with high remanence, high coercive force, and low remanence and coercive force temperature coefficients, and can be used for a long time at high temperatures.
[0003] CN104575899A discloses a sintered NdFeB magnet and a preparation method thereof. The composition of the sintered NdFeB magnet is (RE) a Fe b M c Co d B e , wherein RE is a rare earth metal element, M is one or more of Cu, Al, Ga, Za or Nb, and 28≦a≦33, 0<c≦5, 0<d≦2, 0<e≦1.5, b=100-acde, and a sintered NdFeB magnet is obtained by mixing raw material powders, pressing, vacuum sintering and tempering.
[0004] CN108231394A discloses a low-temperature preparation method for a high-coercivity NdFeB magnet, which comprises preparing a heavy rare earth film on the surface of a sintered NdFeB magnet by magnetron sputtering, then subjecting the film to an ion beam assisted vacuum thermal diffusion treatment process, and finally subjecting the high-coercivity NdFeB magnet to a tempering treatment.
[0005] The traditional alloying process increases the coercivity of the magnet by directly adding heavy rare earth elements to the magnet during the smelting stage. Since heavy rare earth elements will form antiferromagnetic coupling with Fe elements, the remanence and maximum magnetic energy product of the magnet will be greatly reduced. In addition, the direct addition of heavy rare earth elements will also greatly increase the cost of the magnet. Compared with the traditional alloying process, the grain boundary diffusion process can greatly improve the coercivity and temperature stability of the magnet without basically reducing the remanence and maximum magnetic energy product of the magnet, and can save a large amount of heavy rare earth resources. However, the traditional grain boundary diffusion process has problems such as low diffusion efficiency, limited diffusion depth, and uneven diffusion. In view of the defects and shortcomings of the above-mentioned traditional grain boundary diffusion process, it is urgent to study a low-cost grain boundary diffusion technology that can improve diffusion efficiency, diffusion depth, and diffusion uniformity. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets. In the preparation method of the present invention, the composition of NdFeB magnetic powder is designed according to low rare earth content and high Fe content, which ensures that the NdFeB magnet has high residual magnetic induction intensity and maximum magnetic energy product; by using the atomic layer deposition method to deposit a thin film on the surface of the NdFeB magnetic powder, the coercive force and temperature stability of the NdFeB magnet are greatly improved, and the amount of heavy rare earth is reduced. The preparation method of the present invention is simple to operate and easy to control.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] The present invention provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, wherein a thin film is deposited on the surface of NdFeB magnetic powder by an atomic layer deposition method, and then the NdFeB magnet is obtained by orientation pressing, heat preservation sintering and tempering treatment.
[0009] The film contains one or at least two elements of Al, Cu, Er, Hf, Dy, Tb, Ga, La, Ta, Mg, Ti, Ir, Pt, Pd, Co or Ca.
[0010] In the present invention, the film contains one or at least two elements selected from the group consisting of Al, Cu, Er, Hf, Dy, Tb, Ga, La, Ta, Mg, Ti, Ir, Pt, Pd, Co and Ca. Typical but non-limiting examples include Al and Cu, Er and Hf, Dy and La, Tb and Ga, Ta and Mg, Ti and Ir, Pt and Pd, Co and Ca, etc.
[0011] The present invention deposits a thin film on the surface of NdFeB magnetic powder by atomic layer deposition, and coats the surface of the magnetic powder with elements that can enhance the coercive force and temperature stability of the magnet. Since the thin film prepared by the atomic layer deposition system is at the nanometer level, the coating thickness of each cycle is about 1 angstrom, which can not only accurately control the thickness of the thin film layer, but also greatly reduce the amount of heavy rare earth used.
[0012] In addition, after nano-level coating on the surface of the magnetic powder, followed by subsequent oriented pressing, heat preservation sintering and tempering treatment, the thin film on the surface of the magnetic powder can be fully diffused inside the blank, so that this diffusion process is not affected by the diffusion depth and diffusion uniformity compared to the traditional diffusion process, and can also greatly improve the utilization rate of heavy rare earths and the diffusion efficiency of the magnet.
[0013] As a preferred technical solution of the present invention, the composition of the film includes any one or a combination of at least two of a metal element, oxide, nitride, carbide, fluoride or polymer containing the element. Typical but non-limiting examples include: a metal element and an oxide, a nitride and a carbide, a fluoride and a polymer, an oxide and a carbide, etc.
[0014] Preferably, the metal element includes any one of Ir, Pt, Pd, Co, Al or Cu, or a combination of at least two of them. Typical but non-limiting examples include: a combination of Ir and Pt, a combination of Pd and Co, a combination of Co and Al, or a combination of Al and Cu, etc.
[0015] The oxide includes Al 2 O 3 ,CuO,Er 2 O 3 , HfO 2 ,La 2 O 3 , MgO or TiO 2 Any one or a combination of at least two of the following, typical but non-limiting examples are: Al 2 O 3 Combination with CuO, Er 2 O 3 and HfO 2 Combination of HfO 2 and La 2 O 3 A combination of MgO and TiO 2 combinations of etc.
[0016] The nitride includes AlN and / or GaN; the carbide includes TaC and / or TiC.
[0017] The fluoride includes CaF 2 、LaF 3 MgF 2 or DyF 3 Typical but non-limiting examples include: CaF 2 and LaF 3 Combination of CaF 2 and MgF 2 Combination of CaF 2 and DyF 3 Combination of MgF 2 and DyF 3 combinations of etc.
[0018] The polymer includes PMDA-DAH and / or PMDA-ODA.
[0019] As a preferred technical solution of the present invention, the thickness of the film is 0.1 to 50 nm, for example, 0.1 nm, 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0020] As a preferred technical solution of the present invention, the chemical formula of the NdFeB magnetic powder is R a (Fe,M) b B c , where a, b, and c are the mass fractions of R element, Fe, M element, and B element, respectively, a = 26% to 35%, b = 63.9% to 73.1%, and c = 0.9% to 1.1%;
[0021] Among them, the R element is selected from one or at least two elements of rare earth elements, and the M element is selected from one or at least two elements of Co, Cu, Al, Zr, Ga, Ta, Ti, Hf, Cr, Ni, W, Mo or Nb.
[0022] In the present invention, the composition of the NdFeB magnetic powder is designed according to low rare earth content and high Fe content. The lower rare earth content and higher Fe content can ensure that the original NdFeB magnetic powder has higher residual magnetic induction intensity and maximum magnetic energy product.
[0023] In the present invention, the M element is an element that can enhance the coercive force of the magnet and increase the Curie temperature and thermal stability of the magnet.
[0024] In the present invention, a=26% to 35%, and the value of a can be, for example, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0025] In the present invention, b=63.9%~73.1%, and the value of b can be, for example, 63.9%, 64.0%, 65.5%, 66.5%, 67.5%, 68.5%, 69.5%, 70.5%, 71.5%, 73.1%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0026] In the present invention, c=0.9%~1.1%, and the value of c can be, for example, 0.9%, 0.95%, 1.0%, 1.05%, 1.06%, 1.07%, 1.08%, 1.09%, 1.1%, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0027] In the present invention, the R element is selected from one or at least two rare earth elements, and typical but non-limiting examples include: Pr and Nd, Tb and Dy, Eu and La, Ce and Sc, Pr and Dy, etc.
[0028] In the present invention, the M element is selected from one or at least two elements of Co, Cu, Al, Zr, Ga, Ta, Ti, Hf, Cr, Ni, W, Mo or Nb. Typical but non-limiting examples include: Co and Cu, Al and Zr, Ga and Ta, Ti and Hf, Cr and Ni, W and Mo, W and Nb, etc.
[0029] As a preferred technical solution of the present invention, the powder particle size D of the NdFeB magnetic powder is 50 It is 2 to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0030] Preferably, the method for preparing the NdFeB magnetic powder comprises: melting and rapidly solidifying raw materials into alloy casting sheets, and then subjecting the raw materials to hydrogen crushing and air flow milling to obtain the NdFeB magnetic powder.
[0031] Preferably, the temperature of the hydrogen rupture is 400-550°C, for example 400°C, 420°C, 440°C, 450°C, 470°C, 500°C, 520°C, 540°C, 550°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0032] The hydrogen rupture pressure is 0.050-0.10 MPa, for example, 0.050 MPa, 0.060 MPa, 0.070 MPa, 0.080 MPa, 0.090 MPa, 0.10 MPa, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0033] Preferably, the jet mill utilizes high-speed nitrogen to further break up the alloy flakes.
[0034] As a preferred technical solution of the present invention, the atomic layer deposition method includes: placing NdFeB magnetic powder in an atomic layer deposition (ALD) system reaction chamber, evacuating the chamber, setting the ALD source pressure, flow rate, reaction temperature and number of cycles, and depositing a thin film on the surface of the NdFeB magnetic powder.
[0035] Preferably, after the vacuuming, the pressure of the reaction chamber is 5-10Pa, for example 5Pa, 6Pa, 7Pa, 8Pa, 9Pa, 10Pa, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0036] Preferably, the ALD source pressure is 50-100 Pa, for example, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 100 Pa, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0037] The flow rate is 0 to 500 sccm, for example, 0 sccm, 50 sccm, 100 sccm, 150 sccm, 200 sccm, 250 sccm, 300 sccm, 350 sccm, 400 sccm, 450 sccm, 500 sccm, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0038] The reaction temperature is 25-300°C, for example 25°C, 50°C, 100°C, 150°C, 200°C, 250°C, 300°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0039] The reaction temperature defined in the present invention can avoid the problem that the NdFeB magnetic powder is easily oxidized at high temperature.
[0040] The number of cycles is 1 to 60 cycles, for example 1 cycle, 5 cycles, 10 cycles, 20 cycles, 25 cycles, 30 cycles, 40 cycles, 45 cycles, 50 cycles, 55 cycles, 60 cycles, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0041] As a preferred technical solution of the present invention, the magnetic field strength of the orientation pressing is 1-3T, such as 1T, 1.5T, 2T, 2.5T, 3T, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0042] As a preferred technical solution of the present invention, the heat preservation sintering includes primary heat preservation, secondary heat preservation, tertiary heat preservation and sintering performed in sequence.
[0043] Preferably, the primary insulation temperature is 300-400°C, for example 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0044] The temperature of the secondary insulation is 600-700°C, for example 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0045] The temperatures of the three insulations are 800-900°C, for example, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, etc., but are not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0046] In the present invention, the green body after orientation pressing is kept warm at a relatively low temperature, so as to remove the magnetic powder gas and the antioxidant, which is beneficial to the subsequent improvement of the residual magnetic induction intensity, the coercive force and the maximum magnetic energy product of the magnet.
[0047] The sintering temperature is 1050-1100°C, for example, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable; the sintering time is 2-4h, for example, 2h, 2.5h, 3h, 3.5h, 4h, etc., but is not limited to the listed values, and other values not listed in the above numerical range are also applicable.
[0048] As a preferred technical solution of the present invention, the tempering treatment includes primary tempering and secondary tempering.
[0049] Preferably, the primary tempering temperature is 850-900°C, for example 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0050] The time for the primary tempering is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0051] Preferably, the temperature of the secondary tempering is 450-500°C, for example 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0052] The secondary tempering time is 1 to 3 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.5 hours, 3 hours, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0053] Compared with the prior art, the present invention has at least the following beneficial effects:
[0054] (1) The NdFeB magnetic composition of the present invention is designed with low rare earth content and high Fe content. The low rare earth content and high Fe content can ensure that the original magnet has a high residual magnetic induction intensity and maximum magnetic energy product, which is conducive to the magnet maintaining high magnetic properties and thermal stability;
[0055] (2) The present invention deposits a thin film on the surface of NdFeB magnetic powder by atomic layer deposition, which can not only accurately control the thickness of the coating layer, but also greatly reduce the amount of heavy rare earth. After orientation pressing, heat preservation sintering and tempering treatment, the thin film on the surface of the magnetic powder can be fully diffused inside the blank. Compared with the traditional diffusion process, this diffusion process is not affected by the diffusion depth and diffusion uniformity, and can also greatly improve the utilization rate of heavy rare earth and the diffusion efficiency of the magnet;
[0056] (3) The present invention significantly improves the coercive force and temperature stability while ensuring that the magnetic properties such as the residual magnetic induction intensity and the maximum magnetic energy product of the magnet are almost unchanged, and the amount of heavy rare earth used is significantly reduced. The operation is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is a flow chart of the traditional alloy process, the traditional grain boundary diffusion process and the new grain boundary diffusion process of the present invention. DETAILED DESCRIPTION
[0058] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.
[0059] Example 1
[0060] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0061] The composition is (PrNd) 30 Fe 68.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0062] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.096 MPa, and the temperature was 500 °C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0063] NdFeB magnetic powder was placed in the reaction chamber of the atomic layer deposition (ALD) system, the vacuum was pumped to 5Pa, and a Dy source was introduced to react with the NdFeB magnetic powder. 2 Purge the excess reaction gas; then introduce the F source to react, so that DyF 3 The film is deposited on the surface of NdFeB magnetic powder particles, and the film thickness is 0.1nm; the ALD source pressure partial pressure is set to 70Pa, the flow rate is 200sccm, the reaction temperature is 100℃, and the cycle period is 30 cycles;
[0064] DyF will be deposited 3 The magnetic powder of the thin film is oriented and pressed under a 2T magnetic field; the pressed body is then kept at three temperatures of 350℃, 620℃ and 860℃ to remove the magnetic powder gas and antioxidant, and then kept at 1080℃ for 2h for sintering and densification. The first-level tempering temperature is 890℃, the holding time is 1h, the second-level tempering temperature is 480℃, the holding time is 2h, and finally the magnet is machined to obtain NdFeB magnet.
[0065] Example 2
[0066] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0067] The composition is (DyNd) 30 Fe 68.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0068] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.050 MPa, and the temperature was 400 °C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0069] NdFeB magnetic powder was placed in the reaction chamber of the atomic layer deposition (ALD) system, the vacuum was pumped to 10Pa, Al source was introduced to react with NdFeB magnetic powder, and N 2 Purge the excess reaction gas; then introduce the O source to react, so that Al 2 O 3 The film is deposited on the surface of NdFeB magnetic powder particles, and the film thickness is 10nm; the ALD source pressure partial pressure is set to 50Pa, the flow rate is 100sccm, the reaction temperature is 150℃, and the cycle period is 20 cycles;
[0070] Al will be deposited 2 O 3 The magnetic powder of the thin film is oriented and pressed under a 3T magnetic field; the pressed body is then kept at three temperatures of 400℃, 700℃ and 900℃ to remove the magnetic powder gas and antioxidant, and then kept at 1050℃ for 4h for sintering and densification. The first-level tempering temperature is 850℃, the holding time is 1.5h, the second-level tempering temperature is 450℃, the holding time is 3h, and finally the magnet is machined to obtain NdFeB magnet.
[0071] Example 3
[0072] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0073] The composition is (TbNd) 30 Fe 68.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0074] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.01 MPa, and the temperature was 550°C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0075] NdFeB magnetic powder was placed in the reaction chamber of the atomic layer deposition (ALD) system, the vacuum was pumped to 7Pa, and a Ti source was introduced to react with the NdFeB magnetic powder. 2 Excess reaction gas was purged; then C source was introduced for reaction, so that TiC film was deposited on the surface of NdFeB magnetic powder particles, and the film thickness was 50nm; the ALD source pressure partial pressure was set to 100Pa, the flow rate was 500sccm, the reaction temperature was 300℃, and the cycle period was 60 cycles;
[0076] The magnetic powder deposited with TiC film is oriented and pressed under a 3T magnetic field; the pressed body is then kept at three temperatures of 400°C, 700°C, and 900°C to remove the magnetic powder gas and antioxidant, and then kept at 1050°C for 4 hours for sintering and densification. The first-level tempering temperature is 850°C, the holding time is 1.5 hours, the second-level tempering temperature is 450°C, the holding time is 3 hours, and finally the magnet is machined to obtain NdFeB magnet.
[0077] Example 4
[0078] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets. The only difference from Embodiment 1 is that Co metal is deposited on the surface of NdFeB magnetic powder by atomic layer deposition, and the rest is the same as Embodiment 1.
[0079] Example 5
[0080] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets. The only difference from Embodiment 1 is that GaN is deposited on the surface of NdFeB magnetic powder by atomic layer deposition, and the rest is the same as Embodiment 1.
[0081] Example 6
[0082] This embodiment provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets. The only difference from Embodiment 1 is that PMDA-DAH is deposited on the surface of NdFeB magnetic powder by atomic layer deposition, and the rest is the same as Embodiment 1.
[0083] Comparative Example 1
[0084] This comparative example provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0085] The composition is (PrNd) 30 Fe 68.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0086] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.096 MPa, and the temperature was 500 °C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0087] The NdFeB magnetic powder is oriented and pressed under a 2T magnetic field; the pressed body is then kept at three temperatures of 350°C, 620°C, and 860°C to remove the magnetic powder gas and antioxidant, and then kept at 1080°C for 2 hours for sintering and densification. The first-level tempering temperature is 890°C and the holding time is 1 hour. The second-level tempering temperature is 480°C and the holding time is 2 hours. Finally, the magnet is machined to obtain the NdFeB magnet.
[0088] Comparative Example 2
[0089] This comparative example provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0090] The composition is (PrNd, Dy) 31 Fe 67.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0091] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.096 MPa, and the temperature was 500 °C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0092] The NdFeB magnetic powder is oriented and pressed under a 2T magnetic field; the pressed body is then kept at three temperatures of 350°C, 620°C, and 860°C to remove the magnetic powder gas and antioxidant, and then kept at 1080°C for 2 hours for sintering and densification. The first-level tempering temperature is 890°C and the holding time is 1 hour. The second-level tempering temperature is 480°C and the holding time is 2 hours. Finally, the magnet is machined to obtain the NdFeB magnet.
[0093] Comparative Example 3
[0094] This comparative example provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets, comprising:
[0095] The composition is (PrNd) 30 Fe 68.14 Co 0.5 Cu 0.1 Al 0.1 Zr 0.1 Ga 0.1 B 0.96 The raw materials are melted and rapidly solidified in a vacuumed melting furnace to form alloy casting sheets;
[0096] The alloy castings were placed in a hydrogen crushing furnace, vacuumed and filled with hydrogen to a pressure of 0.096 MPa, and the temperature was 500 °C for hydrogen absorption and crushing. 2 The airflow accelerates the particles to supersonic speed to break them up, and obtains NdFeB magnetic powder with a particle size D50 of 2 to 5 μm;
[0097] The NdFeB magnetic powder was oriented and pressed under a 2T magnetic field. The pressed green body was then kept at 350℃, 620℃, and 860℃ to remove the magnetic powder gas and antioxidant, and then kept at 1080℃ for 2h for sintering and densification. DyF was deposited on the surface of the sintered NdFeB magnet by magnetron sputtering. 3 The film undergoes a primary tempering temperature of 890°C and a holding time of 1 h, a secondary tempering temperature of 480°C and a holding time of 2 h, and finally the magnet is mechanically processed to obtain a NdFeB magnet.
[0098] Performance Testing
[0099] The residual magnetic induction intensity B of the NdFeB magnets prepared in the above embodiments and comparative examples is tested. r , intrinsic coercivity H cj , maximum magnetic energy product (BH) max , remanence temperature coefficient α(B r )20~150℃ and intrinsic coercivity temperature coefficient α(H cj )20~150℃, the test results are shown in Table 1.
[0100] Table 1
[0101]
[0102] It can be seen from Table 1 that the NdFeB magnets prepared in Examples 1-6 have a residual magnetic induction intensity B of r 、Maximum magnetic energy product (BH) max When the magnetic properties are almost unchanged, the intrinsic coercive force H cj And temperature stability is greatly improved.
[0103] By comparing Example 1 with Comparative Example 1, it can be seen that in Comparative Example 1, a thin film is not deposited on the surface of NdFeB magnetic powder by the atomic layer deposition method. Although the prepared NdFeB magnet maintains a relatively high residual magnetic induction intensity B r and maximum energy product (BH) max , but the intrinsic coercivity H cj And temperature stability is poor.
[0104] By comparing Example 1 with Comparative Example 2, it can be seen that in Comparative Example 2, the heavy rare earth element is directly dissolved in the composition during the smelting stage, so that the residual magnetic induction intensity B of the prepared NdFeB magnet is r and maximum energy product (BH) max The decrease is large, and the improvement of the coercive force and temperature stability of the magnet is also very limited.
[0105] By comparing Example 1 with Comparative Example 3, it can be seen that in Comparative Example 3, the NdFeB magnet is prepared by the conventional grain boundary diffusion method. Although the magnet maintains a relatively high residual magnetic induction intensity B r and maximum energy product (BH) max , and to a certain extent, the coercive force and temperature stability of the magnet are improved, but due to the influence of diffusion depth and diffusion uniformity, the improvement in the coercive force and temperature stability of the magnet is still not as good as the new grain boundary diffusion technology (atomic layer deposition technology) of the present invention.
[0106] In summary, the present invention provides a preparation method for improving the coercive force and temperature stability of NdFeB magnets. A thin film is deposited on the surface of NdFeB magnetic powder by atomic layer deposition, and oriented pressing, heat preservation sintering and tempering are performed so that the surface film of NdFeB magnetic powder can be fully diffused inside the blank. While ensuring that the magnetic properties such as the residual magnetic induction intensity and the maximum magnetic energy product of the magnet are almost not reduced, the coercive force and temperature stability of the magnet are greatly improved, and the amount of heavy rare earth used is significantly reduced. The method is simple to operate and easy to control.
[0107] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A preparation method for improving the coercive force and temperature stability of NdFeB magnets, characterized in that: A thin film is deposited on the surface of NdFeB magnetic powder by atomic layer deposition, and then the NdFeB magnet is obtained by orientation pressing, heat preservation sintering and tempering. The film contains one or at least two elements of Al, Cu, Er, Hf, Dy, Tb, Ga, La, Ta, Mg, Ti, Ir, Pt, Pd, Co or Ca.
2. The preparation method according to claim 1, characterized in that: The composition of the film includes any one or a combination of at least two of a metal element, an oxide, a nitride, a carbide, a fluoride or a polymer containing the element; Preferably, the metal element includes any one of Ir, Pt, Pd, Co, Al or Cu, or a combination of at least two of them; the oxide includes any one of Al2O3, CuO, Er2O3, HfO2, La2O3, MgO or TiO2, or a combination of at least two of them; the nitride includes AlN and / or GaN; the carbide includes TaC and / or TiC; the fluoride includes any one of CaF2, LaF3, MgF2 or DyF3, or a combination of at least two of them; the polymer includes PMDA-DAH and / or PMDA-ODA.
3. The preparation method according to claim 1 or 2, characterized in that: The thickness of the film is 0.1-50 nm.
4. The preparation method according to any one of claims 1 to 3, characterized in that The chemical formula of the NdFeB magnetic powder is R a (Fe,M) b B c , where a, b, and c are the mass fractions of R element, Fe, M element, and B element, respectively, a = 26% to 35%, b = 63.9% to 73.1%, and c = 0.9% to 1.1%; Among them, the R element is selected from one or at least two elements of rare earth elements, and the M element is selected from one or at least two elements of Co, Cu, Al, Zr, Ga, Ta, Ti, Hf, Cr, Ni, W, Mo or Nb.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The powder particle size D of the NdFeB magnetic powder 50 2~5μm.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The atomic layer deposition method comprises: placing NdFeB magnetic powder in an atomic layer deposition (ALD) system reaction chamber, evacuating the chamber, setting ALD source pressure, flow rate, reaction temperature and cycle times, and depositing a thin film on the surface of the NdFeB magnetic powder.
7. The preparation method according to claim 6, characterized in that: After the vacuum is drawn, the pressure of the reaction chamber is 5-10 Pa; Preferably, the ALD source pressure is 50-100 Pa; the flow rate is 0-500 sccm; the reaction temperature is 25-300° C.; and the number of cycles is 1-60 cycles.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The magnetic field strength of the orientation pressing is 1-3T.
9. The preparation method according to any one of claims 1 to 8, characterized in that: The heat preservation sintering includes primary heat preservation, secondary heat preservation, tertiary heat preservation and sintering performed in sequence; Preferably, the temperature of the first insulation is 300-400°C; the temperature of the second insulation is 600-700°C; the temperature of the third insulation is 800-900°C; the temperature of the sintering is 1050-1100°C, and the sintering time is 2-4h.
10. The preparation method according to any one of claims 1 to 9, characterized in that: The tempering treatment includes primary tempering and secondary tempering; Preferably, the temperature of the first-stage tempering is 850-900° C.; the time of the first-stage tempering is 1-2 hours; Preferably, the temperature of the secondary tempering is 450-500° C.; and the time of the secondary tempering is 1-3 hours.
Citation Information
Patent Citations
Sintered neodymium iron boron magnet and preparation method thereof
CN104575899A
Low-temperature preparation method of high-coercivity neodymium-iron-boron magnet
CN108231394A